Mental health discourse of Malaysian women on social media - Azizan, Awis Rumaisya; Ariffin, Adlina (Universiti Teknologi Malaysia, 2024)
This study delves into the psychological well-being of Malaysian women amidst the unprecedented challenges posed by the COVID-19 pandemic. By examining the discourse prevalent among Malaysian women on social media, particularly on Facebook, we seek to gain insights into their experiences and concerns during the pandemic. Public posts made during the COVID-19 period were systematically collected and assembled into a corpus utilising Lancsbox software. Through a careful analysis of this corpus, the study unveils the frequency and patterns of the topics written by Malaysian women. Moreover, it explores the contexts that shape these posts. Our research aims to shed light on the mental and emotional landscape of Malaysian women as reflected in their online interactions. The findings from this investigation hold the potential to offer valuable guidance to women and relevant stakeholders, contributing to a better understanding of how to support women's mental health within the realm of social media.